PENERAPAN PROJECT-BASED LEARNING BERBASIS STEAM DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KEWIRAUSAHAAN SISWA SEKOLAH DASAR - Fitriana, Erwinda; Ana Fitrotun Nisa; Heri Maria Zulfiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to explore and analyze the effects of implementing Project-Based Learning (PjBL) based on STEAM (Science, Technology, Engineering, Arts, Mathematics) in Natural and Social Sciences (IPAS) education on the development of critical thinking and entrepreneurship skills in elementary school students. The method used in this research is descriptive qualitative, involving the principal and classroom teachers at Purwobinangun Primary School as informants. Data were collected through observation and documentation and analyzed using the Miles and Hubberman model, which includes data reduction, data presentation, and data verification. The results of the study indicate that the implementation of STEAM-based PjBL significantly enhances students' critical thinking skills. Students are better able to identify problems, analyze information, and evaluate various solutions generated. Additionally, there is an improvement in students' abilities to solve complex problems, take risks, and innovate—skills essential for entrepreneurship. The learning process also encourages collaboration and teamwork, which are crucial in the business and entrepreneurial world.